Degradable PVC (polyvinyl chloride) plastic particles as well as preparation method and application thereof

Through the combination of polylactic acid, polyadipic acid/butylene terephthalate and polycaprolactone with chemically modified PVC resin and modified filler, the performance of PVC materials under photothermal conditions is solved. The problem of stability achieves the improvement of stability and safety during use, while ensuring the biodegradability and high-temperature wear resistance of the material.

CN119144104AInactive Publication Date: 2024-12-17DEZHOU VOCATIONAL & TECHN COLLEGE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411411192.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing degradable PVC materials are unstable during use under photothermal conditions, and are prone to air leakage or rupture, which poses safety hazards. At the same time, while improving the degradation performance, it often damages the usability of the material.

Method used

Polylactic acid, polyadipic acid/butylene terephthalate and polycaprolactone of specific ratios are used as biodegradable materials, and a network structure is formed by a combination of chemically modified PVC resin and modified filler. To improve tensile strength and elongation at break, while strengthening the compatibility and interface bonding force of the material by modifying the filler.

Benefits of technology

It realizes PVC plastic particles with stable performance and safe performance during use, which can biodegrade well after being discarded, and maintain good wear resistance and thermal stability under photoaging and high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005078031920000121
    Figure BDA0005078031920000121
  • Figure BDA0005078031920000131
    Figure BDA0005078031920000131
Patent Text Reader

Abstract

The invention provides degradable PVC (polyvinyl chloride) plastic particles as well as a preparation method and application thereof, and belongs to the technical field of PVC plastics, the degradable PVC plastic particles are prepared from the following raw materials in parts by weight: 65 to 70 parts of modified PVC resin, 25 to 30 parts of degradation agent, 5 to 9 parts of modified filler, 4 to 7 parts of plasticizer, 0.2 to 0.6 part of lubricant and 0.2 to 0.4 part of heat stabilizer. The PVC plastic particles prepared by the invention have good stability under light and heat conditions, can be biodegraded, and do not influence the usability of the material, so that the safety and stability of a product prepared from the material are ensured, and the PVC plastic particles have excellent mechanical properties and good wear resistance under high temperature conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PVC plastics, and in particular relates to degradable PVC plastic particles and a preparation method and application thereof. Background Art

[0002] PVC (polyvinyl chloride) is a common synthetic thermoplastic polymer that occupies an important position in the global plastics market. PVC is widely used in many fields, including construction, packaging, furniture, clothing, automobiles and other industries due to its excellent physical properties and low cost.

[0003] In recent years, with the improvement of environmental awareness, people have begun to explore ways to make PVC materials more environmentally friendly. Currently, there are several ways to prepare degradable PVC: (1) Photodegradable PVC: By adding photosensitizers to PVC, the material can be decomposed into smaller molecules under light conditions. (2) Biodegradable PVC: By adding certain biodegradable additives, PVC can be decomposed by microorganisms in a specific environment (such as soil, composting conditions). (3) Chemically modified PVC: By modifying the chemical structure of PVC, it is easier to be decomposed by factors in the environment (such as humidity, temperature, ultraviolet rays, etc.). However, while the existing technology improves the degradation performance of PVC, it often destroys the usability of PVC.

[0004] The main material of the swimming ring is PVC. If the PVC used in the swimming ring is easily degraded under the light and heat conditions at the seaside when used frequently, it may leak or crack after long-term use, posing a serious safety hazard. However, since most degradation is complex, it is urgent to develop a PVC plastic that is stable and safe during use and can be degraded after being discarded. Summary of the invention

[0005] The purpose of the present invention is to provide a degradable PVC plastic particle and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A degradable PVC plastic particle comprises the following raw materials in parts by weight: 65-70 parts of modified PVC resin, 25-30 parts of degradation agent, 5-9 parts of modified filler, 4-7 parts of plasticizer, 0.2-0.6 parts of lubricant and 0.2-0.4 parts of heat stabilizer.

[0008] Furthermore, the degradation agent is a mixture of polylactic acid, polybutylene adipate / terephthalate and polycaprolactone in a weight ratio of 1:(1.2-1.4):(0.6-0.8).

[0009] Polylactic acid was purchased from Shenzhen Guanghua Weiye Co., Ltd. with the product brand name eSunBio3025C.

[0010] Polybutylene adipate / terephthalate was purchased from Inner Mongolia Dongyuan Technology Group Co., Ltd., with a density of 1.18 g / mL-1.3 g / mL.

[0011] Polycaprolactone was purchased from Shenzhen Guanghua Weiye Co., Ltd., product brand Esun500C.

[0012] In the prior art, polycaprolactone is usually added to PVC plastic as a biodegradable material to improve the degradability of PVC plastic, but after adding polylactic acid in the system of the present invention, the thermal stability of PVC plastic is not ideal. The present invention can improve the biodegradability and thermal stability of PVC plastic by adding polylactic acid, polyadipate / butylene terephthalate and polycaprolactone in a specific ratio as biodegradable materials. Analysis shows that the chemical compatibility between different polymers is different, and the polylactic acid, polyadipate / butylene terephthalate and polycaprolactone in a specific ratio are more compatible with other components in the system. At the same time, PLA and PBAT have higher thermal stability, and through synergistic effect, the overall thermal stability performance of PVC material can be affected.

[0013] The preparation method of the modified PVC resin comprises the following steps: by weight, 10 parts of PVC resin, 1.8-2.2 parts of halogenated epoxy compounds, 0.5-0.8 parts of sodium hydroxide, 1.4-1.6 parts of ethanol, 0.5-0.7 parts of water and 0.4-0.6 parts of KH-570 are mixed, added into an open mill, mixed and reacted at a temperature of 160-170° C. for 1.6-1.8 hours, extruded and granulated by an extruder at a temperature of 170-180° C. to obtain the modified PVC resin.

[0014] The addition of polylactic acid, polyadipate / butylene terephthalate and polycaprolactone in a specific ratio in the system of the present invention can cause the tensile strength of PVC plastic to decrease. The present invention attempts to improve the tensile strength of products by modifying PVC materials. Although the physical blending modification of PVC materials is currently widely adopted by the industry to improve tensile strength, it often sacrifices elongation at break, which may be due to the easy formation of defects at the interface formed by physical blending, which will affect the overall performance of the material. The present invention can improve the tensile strength and elongation at break of PVC at the same time by chemically modifying PVC resin. By opening the ring of the halogenated epoxy compound composed of a specific ratio and reacting with the chlorine atoms on the PVC chain to form a new chemical bond, the halogenated epoxy compound is cross-linked with the PVC chain to form a mesh structure, which can improve the tensile strength and elongation at break of PVC at the same time.

[0015] Furthermore, the halogenated epoxy compound comprises 1,2-epichlorobutane, epichlorohydrin and methyl epichlorohydrin in a weight ratio of 1:(1.4-1.7):(0.3-0.5).

[0016] Furthermore, the PVC resin includes a mixture of PVC resin I, PVC resin II and PVC resin III in a weight ratio of 1:(1.3-1.5):(0.3-0.5).

[0017] Further, PVC resin I: degree of polymerization is 980-846, apparent density is 0.45g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-6. PVC resin II: degree of polymerization is 740-650, apparent density is 0.42g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-8. PVC resin III: degree of polymerization is 1135-981, apparent density is 0.48g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-5.

[0018] Methyl epichlorohydrin, CAS: 598-09-4.

[0019] Epichlorohydrin, CAS: 106-89-8.

[0020] 1,2-Epoxychlorobutane, CAS: 13067-79-3

[0021] Furthermore, the preparation method of the modified filler comprises the following steps:

[0022] (1) mixing cerium dioxide, boron nitride and titanium dioxide to obtain a filler;

[0023] (2) 1 g of filler, 0.4-0.6 mL of KH570, 18-20 mL of ethanol and 3-5 mL of deionized water were mixed, refluxed at 80-85° C. for 4-6 h, filtered and dried to obtain a silane-modified filler;

[0024] (3) p-Aminostyrene, 3-mercaptopropyltrimethoxysilane (CAS: 4420-74-0) and tetrahydrofuran in a molar ratio of 1:1 are mixed, and the mixture is reacted for 26-30 hours at 25-30° C. and a light intensity of 1000 to 5000 lux to obtain an intermediate. 2-2.5 mL of aniline is added to hydrochloric acid, and the pH value is adjusted to 2.0-2.2. 0.4-0.6 g of the intermediate, 5 mg of silane-modified filler and ammonium persulfate are continuously added, and the mixture is reacted at a temperature of 3-5° C. for 18-20 hours. The mixture is filtered and dried to obtain a modified filler.

[0025] Furthermore, the weight ratio of cerium dioxide, boron nitride and titanium dioxide is 1:(1.3-1.5):(0.3-0.6).

[0026] Furthermore, the average particle size of cerium dioxide is 30nm, the particle size range is 20-50nm, and the specific surface area is 110m 2 / g; the average particle size of boron nitride is 100nm, the particle size range is 50-200nm, and the specific surface area is 19m 2 / g; the average particle size of titanium dioxide is 10nm, the particle size range is 4-20nm, and the specific surface area is 70-90m 2 / g. Purchased from Ningbo Jinlei Nanomaterial Technology Co., Ltd.

[0027] The present invention attempts to improve the wear resistance of PVC plastic by adding fillers, but the effect is not ideal. By modifying the filler and forming a layer of polyaniline containing silicon-oxygen bonds on the surface of the modified filler, the compatibility of the filler with other components can be improved, and the room temperature wear resistance of the PVC plastic can be improved. And when a PVC resin composed of cerium dioxide, boron nitride and titanium dioxide with specific parameters and proportions and a mixture of PVC resin I, PVC resin II and PVC resin III with specific parameters and proportions is used at the same time, the wear resistance of the PVC plastic under light aging conditions can be improved. The analysis shows that the dispersion of the modified filler and the PVC resin is more uniform, and the silicon-oxygen bonds can enhance the interfacial bonding between the filler and the PVC matrix.

[0028] Furthermore, the amount of ammonium persulfate used is 4-6% of the mass of aniline, and the mass fraction of hydrochloric acid is 12-14%.

[0029] The plasticizer is selected from one or more of phthalates, citrates, phosphates, and aliphatic dibasic acid esters.

[0030] Furthermore, the heat stabilizer is an organotin stabilizer.

[0031] Furthermore, the organic tin stabilizer is methyltin mercaptan, which is purchased from Henan Dazheng Chemical Products Co., Ltd.

[0032] Furthermore, the lubricant is polyethylene wax, purchased from Shanghai Zhenlishi Network Technology Co., Ltd., model AC-629A.

[0033] The present invention also provides a method for preparing the degradable PVC plastic particles, comprising the following steps:

[0034] (1) Mix the raw materials, put them into a high-speed blender, and stir them at 130-150° C. for 15-25 minutes;

[0035] (2) The stirred raw materials are extruded and granulated through a twin-screw extruder to obtain biodegradable PVC plastic particles.

[0036] Furthermore, the screw temperatures of the twin-screw extruder are: zone 1 temperature 140-150°C, zone 2 temperature 150-160°C, zone 3 temperature 135-145°C, zone 4 temperature 135-145°C and zone 5 temperature 130-140°C.

[0037] The present invention also provides application of the degradable PVC plastic particles, and the degradable PVC plastic particles are used for preparing swimming rings.

[0038] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0039] 1. The present invention can improve the biodegradability and thermal stability of PVC plastics by adding polylactic acid, polybutylene adipate / terephthalate and polycaprolactone in a specific ratio as biodegradable materials.

[0040] 2. The present invention can improve the tensile strength and elongation at break of PVC by chemically modifying the PVC resin.

[0041] 3. The present invention can improve the compatibility of the filler with other components and improve the room temperature wear resistance of PVC plastic by modifying the filler.

[0042] 4. In the system of the present invention, when cerium dioxide, boron nitride and titanium dioxide with specific parameters and proportions and PVC resin I, PVC resin II and PVC resin III with specific parameters and proportions are used simultaneously, the wear resistance of PVC plastic under light aging conditions can be improved. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] The present embodiment provides a degradable PVC plastic particle, comprising the following raw materials in parts by weight: 68 parts of modified PVC resin, 27 parts of degradation agent, 8 parts of modified filler, 5 parts of plasticizer, 0.4 parts of lubricant and 0.3 parts of heat stabilizer.

[0046] The plasticizer is phthalate, and the heat stabilizer is methyltin mercaptan, purchased from Henan Dazheng Chemical Products Co., Ltd. The lubricant is polyethylene wax, purchased from Shanghai Zhenlishi Network Technology Co., Ltd., model AC-629A.

[0047] The preparation method of the modified PVC resin comprises the following steps: by weight, 10 parts of PVC resin, 2 parts of halogenated epoxy compound, 0.7 parts of sodium hydroxide, 1.5 parts of ethanol, 0.6 parts of water and 0.5 parts of KH-570 are mixed, added into an open mill, mixed and reacted at a temperature of 165° C. for 17 hours, extruded and granulated by an extruder at a temperature of 175° C., and obtained the modified PVC resin.

[0048] The halogenated epoxy compound includes 1,2-epichlorobutane, epichlorohydrin and methyl epichlorohydrin in a weight ratio of 1:1.6:0.4.

[0049] The PVC resin includes a mixture of PVC resin I, PVC resin II and PVC resin III in a weight ratio of 1:1.4:0.4. PVC resin I: degree of polymerization is 980-846, and the apparent density is 0.45 g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-6. PVC resin II: degree of polymerization is 740-650, and the apparent density is 0.42 g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-8. PVC resin III: degree of polymerization is 1135-981, and the apparent density is 0.48 g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-5.

[0050] The degradation agent is a mixture of polylactic acid, polybutylene adipate / terephthalate and polycaprolactone in a weight ratio of 1:1.3:0.7. Polylactic acid was purchased from Shenzhen Guanghua Weiye Co., Ltd., with a product brand of eSunBio3025C. Polybutylene adipate / terephthalate was purchased from Inner Mongolia Dongyuan Technology Group Co., Ltd., with a density of 1.18g / mL-1.3g / mL. Polycaprolactone was purchased from Shenzhen Guanghua Weiye Co., Ltd., with a product brand of Esun500C.

[0051] The preparation method of the modified filler comprises the following steps:

[0052] (1) mixing cerium dioxide, boron nitride and titanium dioxide in a weight ratio of 1:1.4:0.5 to obtain a filler;

[0053] (2) 1 g of filler, 0.5 mL of KH570, 19 mL of ethanol and 4 mL of deionized water were mixed, refluxed at 82° C. for 5 h, filtered and dried to obtain a silane-modified filler;

[0054] (3) p-Aminostyrene, 3-mercaptopropyltrimethoxysilane and tetrahydrofuran in a molar ratio of 1:1 were mixed and reacted at 27°C and a light intensity of 2000 lux for 28 hours to obtain an intermediate. 2.2 mL of aniline was added to hydrochloric acid with a mass fraction of 13%. The pH value was adjusted to 2.1. 0.5 g of the intermediate, 5 mg of silane-modified filler and ammonium persulfate were added. The amount of ammonium persulfate was 5% of the mass of aniline. The reaction was carried out at a temperature of 4°C for 19 hours, filtered, and dried to obtain a modified filler.

[0055] The average particle size of cerium dioxide is 30nm, the particle size range is 20-50nm, and the specific surface area is 110m 2 / g; the average particle size of boron nitride is 100nm, the particle size range is 50-200nm, and the specific surface area is 19m 2 / g; the average particle size of titanium dioxide is 10nm, the particle size range is 4-20nm, and the specific surface area is 70-90m 2 / g. Purchased from Ningbo Jinlei Nanomaterial Technology Co., Ltd.

[0056] The method for preparing the degradable PVC plastic particles comprises the following steps:

[0057] (1) Mix the raw materials, put them into a high-speed blender, and stir them at 140°C for 20 minutes;

[0058] (2) Extruding the stirred raw materials into granules through a twin-screw extruder, wherein the screw temperatures of the twin-screw extruder are: zone 1 temperature 145° C., zone 2 temperature 155° C., zone 3 temperature 140° C., zone 4 temperature 140° C. and zone 5 temperature 135° C., to obtain degradable PVC plastic granules.

[0059] Example 2

[0060] The present embodiment provides a degradable PVC plastic particle, comprising the following raw materials in parts by weight: 65 parts of modified PVC resin, 30 parts of degradation agent, 5 parts of modified filler, 7 parts of plasticizer, 0.2 parts of lubricant and 0.4 parts of heat stabilizer.

[0061] The plasticizer is phthalate, and the heat stabilizer is methyltin mercaptan, purchased from Henan Dazheng Chemical Products Co., Ltd. The lubricant is polyethylene wax, purchased from Shanghai Zhenlishi Network Technology Co., Ltd., model AC-629A.

[0062] The preparation method of the modified PVC resin comprises the following steps: by weight, 10 parts of PVC resin, 1.8 parts of halogenated epoxy compound, 0.8 parts of sodium hydroxide, 1.4 parts of ethanol, 0.7 parts of water and 0.4 parts of KH-570 are mixed, added into an open mill, mixed and reacted at a temperature of 170° C. for 1.6 hours, extruded and granulated by an extruder at a temperature of 180° C. to obtain the modified PVC resin.

[0063] The halogenated epoxy compound includes 1,2-epichlorobutane, epichlorohydrin and methyl epichlorohydrin in a weight ratio of 1:1.4:0.3.

[0064] The PVC resin includes a mixture of PVC resin I, PVC resin II and PVC resin III in a weight ratio of 1:1.3:0.5. PVC resin I: degree of polymerization is 980-846, and the apparent density is 0.45 g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-6. PVC resin II: degree of polymerization is 740-650, and the apparent density is 0.42 g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-8. PVC resin III: degree of polymerization is 1135-981, and the apparent density is 0.48 g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-5.

[0065] The degradation agent is a mixture of polylactic acid, polybutylene adipate / terephthalate and polycaprolactone in a weight ratio of 1:1.2:0.8. Polylactic acid was purchased from Shenzhen Guanghua Weiye Co., Ltd., with a product brand of eSunBio3025C. Polybutylene adipate / terephthalate was purchased from Inner Mongolia Dongyuan Technology Group Co., Ltd., with a density of 1.18g / mL-1.3g / mL. Polycaprolactone was purchased from Shenzhen Guanghua Weiye Co., Ltd., with a product brand of Esun500C.

[0066] The preparation method of the modified filler comprises the following steps:

[0067] (1) mixing cerium dioxide, boron nitride and titanium dioxide in a weight ratio of 1:1.3:0.6 to obtain a filler;

[0068] (2) 1 g of filler, 0.4 mL of KH570, 20 mL of ethanol and 3 mL of deionized water were mixed, refluxed at 85° C. for 4 h, filtered and dried to obtain a silane-modified filler;

[0069] (3) p-Aminostyrene, 3-mercaptopropyltrimethoxysilane and tetrahydrofuran in a molar ratio of 1:1 were mixed and reacted at 25°C and a light intensity of 5000 lux for 26 hours to obtain an intermediate. 2.5 mL of aniline was added to hydrochloric acid with a mass fraction of 12% and the pH value was adjusted to 2.2. 0.4 g of the intermediate, 5 mg of silane-modified filler and ammonium persulfate were added, with the amount of ammonium persulfate being 6% of the mass of aniline. The reaction was carried out at a temperature of 3°C for 20 hours, filtered, and dried to obtain a modified filler.

[0070] The average particle size of cerium dioxide is 30nm, the particle size range is 20-50nm, and the specific surface area is 110m 2 / g; the average particle size of boron nitride is 100nm, the particle size range is 50-200nm, and the specific surface area is 19m 2 / g; the average particle size of titanium dioxide is 10nm, the particle size range is 4-20nm, and the specific surface area is 70-90m 2 / g. Purchased from Ningbo Jinlei Nanomaterial Technology Co., Ltd.

[0071] The method for preparing the degradable PVC plastic particles comprises the following steps:

[0072] (1) Mix the raw materials, put them into a high-speed blender, and stir them at 150°C for 25 minutes;

[0073] (2) Extruding the stirred raw materials into granules through a twin-screw extruder, wherein the screw temperatures of the twin-screw extruder are: zone 1 temperature 140° C., zone 2 temperature 160° C., zone 3 temperature 135° C., zone 4 temperature 145° C. and zone 5 temperature 130° C., to obtain degradable PVC plastic granules.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 1 is that the halogenated epoxy compound includes 1,2-epichlorobutane, epichlorohydrin and methyl epichlorohydrin in a weight ratio of 1:1:1.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 1 is that the PVC resin includes a mixture of PVC resin I, PVC resin II and PVC resin III in a weight ratio of 1:1:1. PVC resin I: degree of polymerization is 980-846, and the apparent density is 0.45g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-6. PVC resin II: degree of polymerization is 740-650, and the apparent density is 0.42g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-8. PVC resin III: degree of polymerization is 1135-981, and the apparent density is 0.48g / mL. Purchased from Sichuan Jinlu Resin Co., Ltd., model SG-5.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 1 is that the PVC resin includes a mixture of PVC resin I, PVC resin II and PVC resin III in a weight ratio of 1:1.4:0.4. PVC resin I: degree of polymerization of 450, apparent density of 0.60 g / mL, purchased from China Taiwan Plastics Industry Co., Ltd.; PVC resin II: degree of polymerization of 500, apparent density of 0.62 g / mL, purchased from China Taiwan Plastics Industry Co., Ltd.; PVC resin III: degree of polymerization of 800, apparent density of 0.61 g / mL, purchased from LG-BOHAI.

[0080] Comparative Example 4

[0081] The difference between this comparative example and Example 1 is that the degradation agent is polycaprolactone.

[0082] Comparative Example 5

[0083] The difference between this comparative example and Example 1 is that the degradation agent is a mixture of polylactic acid, poly(adipate / butylene terephthalate) and polycaprolactone in a weight ratio of 1:1:1.

[0084] Comparative Example 6

[0085] The difference between this comparative example and Example 1 is that the preparation method of the modified filler comprises the following steps:

[0086] (1) mixing cerium dioxide, boron nitride and titanium dioxide to obtain a filler;

[0087] (2) dissolving vinyltriethoxysilane in anhydrous ethanol to prepare a solution with a mass concentration of 42%;

[0088] (3) Spraying the solution onto the filler in a high-speed mixer, stirring at high speed to make it uniform, drying it in a forced air drying oven at 100° C. for 4 h, and then cooling it naturally to obtain a modified filler.

[0089] Comparative Example 7

[0090] The difference between this comparative example and Example 1 is that the average particle size of cerium dioxide is 1 μm, the particle size range is 0.6-1.4 μm, and the specific surface area is 23 m 2 / g; the average particle size of boron nitride is 500nm, the particle size range is 450-600nm, and the specific surface area is 16m 2 / g; the average particle size of titanium dioxide is 200nm, the particle size range is 100-250nm, and the specific surface area is 50-60m 2 / g. Purchased from Ningbo Jinlei Nanomaterial Technology Co., Ltd.

[0091] Comparative Example 8

[0092] The difference between this comparative example and Example 1 is that cerium dioxide, boron nitride and titanium dioxide are mixed in a weight ratio of 1:1:1 to obtain a filler.

[0093] Performance Testing

[0094] The degradable PVC plastic particles of Examples 1-2 and Comparative Examples 1-8 were prepared into films and subjected to the following performance tests.

[0095] 1. Refer to GB / T3830-2008 to determine the tensile strength and elongation at break of the film.

[0096] 2. Determine the wear resistance according to DIN53516; test the film in an aging test chamber at an exposure temperature of 50°C for a period of 90 days, and then determine the wear resistance after light aging.

[0097] 3. Biodegradation: Refer to GB / T19275-2003, use the soil landfill test method, the landfill time is 90 days, and the biodegradability of the material is evaluated by the average percentage of mass change (%). The higher the value, the better the biodegradability.

[0098] 4. Thermal degradation: Refer to GB / T7141-2008, use gravity convection thermal aging test chamber for testing, exposure temperature 50°C, exposure period 90 days, evaluation standard refer to GB / T20197-2006, use high temperature gel chromatography to measure the weight average relative molecular mass, the result is expressed as weight average molecular mass reduction rate (%), the higher the value, the better the thermal degradation ability. At the same time, measure the tensile strength and elongation at break under this condition.

[0099] 5. Photodegradation: Refer to GB / T16422.2-2014, expose the sample in a xenon lamp artificial accelerated aging box, use a daylight filter for exposure, use a broadband wavelength range of 300nm-400nm, refer to GB / T20197-2006 for evaluation standards, and set the cumulative radiation energy to 26MJ / m 2 , blackboard temperature 65℃±5℃, relative humidity 65%±5%, water spraying cycle 18min±0.5min per spraying, time between two sprayings 102min±0.5min, high temperature gel chromatography to measure weight average molecular weight, the result is expressed as weight average molecular weight reduction rate (%), the higher the value, the better the photodegradation ability. At the same time, the tensile strength and elongation at break under this condition are measured.

[0100] The results are shown in Table 1.

[0101] Table 1 Performance test results

[0102]

[0103]

[0104] It can be seen from the above performance test results that the PVC plastic of Examples 1-2 has good stability under light and heat conditions, and can be biodegraded without affecting the usability of the material, thereby ensuring the safety and stability of the material after it is made into products. At the same time, it has excellent mechanical properties and good wear resistance under high temperature conditions.

[0105] However, the comparative examples are significantly worse than the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the composition of the halogenated epoxy compounds used to prepare the modified PVC resin is different, and it can be seen that the mechanical properties of the PVC plastic are reduced. In comparative example 2, the ratios of PVC resin I, PVC resin II and PVC resin III are different, and in comparative example 3, the parameters of PVC resin I, PVC resin II and PVC resin III are different, and the tensile strength and elongation at break of the PVC plastic are reduced, and the wear resistance at high temperature is also affected. The compositions of the degradation agents in comparative examples 4 and 5 are different, and the thermal stability of the PVC plastic is reduced. In comparative example 6, the filler modification methods are different, and the room temperature wear resistance of the PVC plastic is reduced. In comparative examples 7 and 8, the ratios and parameters of the fillers are different, and the wear resistance of the PVC plastic at high temperatures is reduced. The above experimental results further demonstrate the importance of the technical solutions defined in the present invention for its technical effects.

[0106] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A degradable PVC plastic particle, characterized in that: The invention comprises the following raw materials in parts by weight: 65-70 parts of modified PVC resin, 25-30 parts of degradation agent, 5-9 parts of modified filler, 4-7 parts of plasticizer, 0.2-0.6 parts of lubricant and 0.2-0.4 parts of heat stabilizer; The preparation method of the modified PVC resin comprises the following steps: by weight, 10 parts of PVC resin, 1.8-2.2 parts of halogenated epoxy compounds, 0.5-0.8 parts of sodium hydroxide, 1.4-1.6 parts of ethanol, 0.5-0.7 parts of water and 0.4-0.6 parts of KH-570 are mixed, added into an open mill, mixed and reacted at a temperature of 160-170° C. for 1.6-1.8 hours, extruded and granulated by an extruder at a temperature of 170-180° C. to obtain the modified PVC resin.

2. The degradable PVC plastic particles according to claim 1, characterized in that: The halogenated epoxy compound includes 1,2-epichlorobutane, epichlorohydrin and methyl epichlorohydrin in a weight ratio of 1:(1.4-1.7):(0.3-0.5).

3. The degradable PVC plastic particles according to claim 1, characterized in that: The PVC resin includes PVC resin I, PVC resin II and PVC resin III in a weight ratio of 1: (1.3-1.5): (0.3-0.5); the degree of polymerization of PVC resin I is 980-846, and the apparent density is 0.45 g / mL; the degree of polymerization of PVC resin II is 740-650, and the apparent density is 0.42 g / mL; the degree of polymerization of PVC resin III is 1135-981, and the apparent density is 0.48 g / mL.

4. The degradable PVC plastic particles according to claim 1, characterized in that: The degradation agent is a mixture of polylactic acid, polyadipate / butylene terephthalate and polycaprolactone in a weight ratio of 1: (1.2-1.4): (0.6-0.8).

5. The degradable PVC plastic particles according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: (1) mixing cerium dioxide, boron nitride and titanium dioxide to obtain a filler; (2) 1 g of filler, 0.4-0.6 mL of KH570, 18-20 mL of ethanol and 3-5 mL of deionized water were mixed, refluxed at 80-85° C. for 4-6 h, filtered and dried to obtain a silane-modified filler; (3) p-Aminostyrene, 3-mercaptopropyltrimethoxysilane and tetrahydrofuran in a molar ratio of 1:1 are mixed, and the mixture is reacted for 26-30 hours at 25-30° C. and a light intensity of 1000 to 5000 lux to obtain an intermediate. 2-2.5 mL of aniline is added to hydrochloric acid, and the pH value is adjusted to 2.0-2.

2. 0.4-0.6 g of the intermediate, 5 mg of silane-modified filler and ammonium persulfate are continuously added, and the mixture is reacted at a temperature of 3-5° C. for 18-20 hours. The mixture is filtered and dried to obtain a modified filler.

6. The degradable PVC plastic particles according to claim 5, characterized in that: The weight ratio of cerium dioxide, boron nitride and titanium dioxide is 1:(1.3-1.5):(0.3-0.6).

7. The degradable PVC plastic particles according to claim 6, characterized in that: The average particle size of cerium dioxide is 30nm, the particle size range is 20-50nm, and the specific surface area is 110m 2 / g; the average particle size of boron nitride is 100nm, the particle size range is 50-200nm, and the specific surface area is 19m 2 / g; the average particle size of titanium dioxide is 10nm, the particle size range is 4-20nm, and the specific surface area is 70-90m 2 / g.

8. The degradable PVC plastic particles according to claim 5, characterized in that: The amount of ammonium persulfate used is 4-6% of the mass of aniline, and the mass fraction of hydrochloric acid is 12-14%.

9. A method for preparing the degradable PVC plastic particles according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Mix the raw materials, put them into a high-speed blender, and stir them at 130-150° C. for 15-25 minutes; (2) The stirred raw materials are extruded and granulated through a twin-screw extruder to obtain biodegradable PVC plastic particles.

10. An application of the degradable PVC plastic particles according to any one of claims 1 to 8, characterized in that: The degradable PVC plastic particles are used for preparing swimming rings.

Citation Information

Patent Citations

  • Degradable disintegrable PVC plastic and application thereof

    CN110819040A

  • Preparation method of water-based alkyd anticorrosive paint

    CN115477893A

  • Biodegradable fiber and manufacturing method therefor

    WO2022257394A1